2015
DOI: 10.1016/j.ijrobp.2014.09.031
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy Endpoints of Radiation Therapy Group Protocol 0247: A Randomized, Phase 2 Study of Neoadjuvant Radiation Therapy Plus Concurrent Capecitabine and Irinotecan or Capecitabine and Oxaliplatin for Patients With Locally Advanced Rectal Cancer

Abstract: Purpose/Objectives Primary endpoint analysis of RTOG 0247 demonstrated preoperative RT with capecitabine plus oxaliplatin achieved a pCR pre-specified threshold (21%) to merit further study, whereas the RT with capecitabine plus irinotecan arm did not (10%). Secondary efficacy endpoints are reported here. Methods and Materials A randomized phase II trial evaluated preoperative RT (50.4 Gy in 1.8 Gy fractions) with two concurrent chemotherapy regimens: 1—capecitabine (1200 mg/m2/d M-F) plus irinotecan (50 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 18 publications
2
21
0
Order By: Relevance
“…Similar results were obtained using neoadjuvant single-agent capecitabine plus radiotherapy for LARC [ 26 ]. Recently, cytotoxic agents such as irinotecan and oxaliplatin plus fluorouracil have been administrated for combination chemotherapy regarding NACRT [ 27 , 28 ]. Wong et al reported that the efficacy of capecitabine plus irinotecan with radiotherapy and the efficacy of capecitabine plus oxaliplatin with radiotherapy were similar in a neoadjuvant setting for LARC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained using neoadjuvant single-agent capecitabine plus radiotherapy for LARC [ 26 ]. Recently, cytotoxic agents such as irinotecan and oxaliplatin plus fluorouracil have been administrated for combination chemotherapy regarding NACRT [ 27 , 28 ]. Wong et al reported that the efficacy of capecitabine plus irinotecan with radiotherapy and the efficacy of capecitabine plus oxaliplatin with radiotherapy were similar in a neoadjuvant setting for LARC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, numerous studies reported short and long-term results of NCRT with combination of capecitabine, oxaliplatin, or bevacizumab. However, in many of those studies, the oncologic results were found to be not superior [ 21 22 ], and more significant toxicity and inferior compliance were reported, on the contrary [ 23 ]. Further research will be necessary to confirm that above-mentioned combinations of treatments could obtain more improved prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Other efforts are underway to intensify and improve the efficacy of neoadjuvant treatments. Particular emphasis has been placed on the role of improving the concurrent chemotherapy component of neoadjuvant CRT . To that end, a recently presented phase 2 clinical trial platform is aiming to identify novel sensitizing agents administered with neoadjuvant CRT that might improve disease‐related outcomes .…”
Section: Future Directionsmentioning
confidence: 99%
“…Particular emphasis has been placed on the role of improving the concurrent chemotherapy component of neoadjuvant CRT. 8,63,64 To that end, a recently presented phase 2 clinical trial platform is aiming to identify novel sensitizing agents administered with neoadjuvant CRT that might improve disease-related outcomes. 65 This platform will use a TNT approach, with neoadjuvant FOLFOX followed by CRT and then definitive surgery.…”
Section: Future Directionsmentioning
confidence: 99%